2023
DOI: 10.3389/fimmu.2022.1096551
|View full text |Cite
|
Sign up to set email alerts
|

The crosstalk between the gut microbiota and tumor immunity: Implications for cancer progression and treatment outcomes

Abstract: The gastrointestinal tract is inhabited by trillions of commensal microorganisms that constitute the gut microbiota. As a main metabolic organ, the gut microbiota has co-evolved in a symbiotic relationship with its host, contributing to physiological homeostasis. Recent advances have provided mechanistic insights into the dual role of the gut microbiota in cancer pathogenesis. Particularly, compelling evidence indicates that the gut microbiota exerts regulatory effects on the host immune system to fight agains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 170 publications
(184 reference statements)
2
13
0
Order By: Relevance
“…In the present study, in both nasopharyngeal swabs and stools, every group of patients presented distinctly differentiated clusters. As previously reported, COVID-19 disease severity is more dependent on the presence or absence of certain bacteria rather than alterations in bacterial diversity and richness [14,53]. Supporting this, characterization of bacterial microbiota composition at phyla and genera levels for nasopharyngeal and stool samples indicated a more evident association between changes on them and the severity of the disease.…”
Section: Discussionsupporting
confidence: 78%
“…In the present study, in both nasopharyngeal swabs and stools, every group of patients presented distinctly differentiated clusters. As previously reported, COVID-19 disease severity is more dependent on the presence or absence of certain bacteria rather than alterations in bacterial diversity and richness [14,53]. Supporting this, characterization of bacterial microbiota composition at phyla and genera levels for nasopharyngeal and stool samples indicated a more evident association between changes on them and the severity of the disease.…”
Section: Discussionsupporting
confidence: 78%
“…Intestinal barrier impairment, dysbiosis of gut microbiota, and perturbation of metabolites are prevalent occurrences among individuals with COVID‐19. Extensive research has consistently shown the association between microbiota composition and the morbidity, exacerbation, and mortality rates seen in COVID‐19 patients 51–55 . The gut microbiota facilitates the assessment of sickness severity in individuals with COVID‐19 56 .…”
Section: Discussionmentioning
confidence: 99%
“…patients. [51][52][53][54][55] The gut microbiota facilitates the assessment of sickness severity in individuals with COVID-19. 56 From a mechanical standpoint, it is observed that COVID-19 disrupts the composition of gut microbiota and metabolites.…”
Section: Potential Confounding Factors and Mechanismsmentioning
confidence: 99%
“…The bidirectional regulation between the gut microbiota and host immunity may play an important role in this process. 109 In addition, SARS-CoV-2 may cause the disorder of gut microbiota, thereby increasing susceptibility to COVID-19. The mechanisms by which the disturbance of gut microbiota increases susceptibility to COVID-19 and associated symptoms are poorly understood.…”
Section: 21mentioning
confidence: 99%
“…Subsequently, related bacteria produce bioactive metabolites, inflammatory factor responses, and changes in the immune microenvironment, which may promote the progression of COVID‐19. The bidirectional regulation between the gut microbiota and host immunity may play an important role in this process 109 . In addition, SARS‐CoV‐2 may cause the disorder of gut microbiota, thereby increasing susceptibility to COVID‐19.…”
Section: Dynamic Changes Of Microbiota In Covid‐19mentioning
confidence: 99%